Juxtaposing Design-Based Thinking Practices of Secondary Student-Teachers During the Internship Program: Input for an Improved Pre-Service Training - R. Pecson, Ryan; C. Canare, Laarni; T. Olubia, Leandro; S. Romero, Monina; C. Adraneda, Gemma (Universitas PGRI Madiun, 2024)
Student-teachers need help with creating and evaluating learning resources once deployed in schools. To provide a responsive approach to deal with their situations, the present study examines the design-based thinking practices among secondary student-teachers during their internship program in various secondary schools in the divisions of Bataan and Balanga City, Province of Bataan, Philippines, as input for the improved pre-service training. The design-based thinking practices of student-teachers are examined in terms of understanding (empathizing and defining), exploring (ideating and prototyping), and materializing (testing and implementing). Likewise, the study ascertains if there are significant differences in the design-based thinking practices of student-teachers. Using the descriptive-survey design of quantitative research, the data are gathered from 172 out of 199 student-teachers under the College of Education (COEd) who are randomly selected. The primary data-gathering tool used in the study is an adopted survey questionnaire. The quantitative data gathered from the study will be analyzed using descriptive statistics (i.e., mean and standard deviation) and inferential statistics (i.e., F-test/ANOVA). Results indicate that student-teachers excelled in understanding and exploring phases of design-based thinking but lagged in 'Materializing.' To improve, pre-service training should emphasize practical design thinking applications, workshops, mentorship, technology integration, reflection, collaboration, feedback, and continuous development. At the outset, the study proposes improvements in pre-service training to guide student-teachers in their meaningful integration of design-based thinking in their internship program.Student-teachers need help with creating and evaluating learning resources once deployed in schools. To provide a responsive approach to deal with their situations, the present study examines the design-based thinking practices among secondary student-teachers during their internship program in various secondary schools in the divisions of Bataan and Balanga City, Province of Bataan, Philippines, as input for the improved pre-service training. The design-based thinking practices of student-teachers are examined in terms of understanding (empathizing and defining), exploring (ideating and prototyping), and materializing (testing and implementing). Likewise, the study ascertains if there are significant differences in the design-based thinking practices of student-teachers. Using the descriptive-survey design of quantitative research, the data are gathered from 172 out of 199 student-teachers under the College of Education (COEd) who are randomly selected. The primary data-gathering tool used in the study is an adopted survey questionnaire. The quantitative data gathered from the study will be analyzed using descriptive statistics (i.e., mean and standard deviation) and inferential statistics (i.e., F-test/ANOVA). Results indicate that student-teachers excelled in understanding and exploring phases of design-based thinking but lagged in 'Materializing.' To improve, pre-service training should emphasize practical design thinking applications, workshops, mentorship, technology integration, reflection, collaboration, feedback, and continuous development. At the outset, the study proposes improvements in pre-service training to guide student-teachers in their meaningful integration of design-based thinking in their internship program.